2022
DOI: 10.3390/ijms231911529
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genomic Profiling (CGP)-Informed Personalized Molecular Residual Disease (MRD) Detection: An Exploratory Analysis from the PREDATOR Study of Metastatic Colorectal Cancer (mCRC) Patients Undergoing Surgical Resection

Abstract: A majority of patients with metastatic colorectal cancer (mCRC) experience recurrence post curative-intent surgery. The addition of adjuvant chemotherapy has shown to provide limited survival benefits when applied to all patients. Therefore, a biomarker to assess molecular residual disease (MRD) accurately and guide treatment selection is highly desirable for high-risk patients. This feasibility study evaluated the prognostic value of a tissue comprehensive genomic profiling (CGP)-informed, personalized circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…By designing the sensitivity study samples with 2 monitorable alterations, we sought to estimate lowest possible sensitivity of the assay and show it to be >97.3% in low ctDNA samples (5–10 MTM/mL). Sensitivity and precision of the assay will be less reliable at lower levels of ctDNA, however recent data suggests the assay is capable of detecting ctDNA down to the 0.4 MTM/mL level in metastatic colorectal cancer [ 2 ], and the performance of assay is sufficient to identify response to immunotherapy in patients with metastatic cancer [ 13 , 35 ] To address the possible limitation of evaluable patients, we show that 90.0% of patients with tissue CGP would have ≥2 monitorable alterations ( Fig 2B ). This was consistent among many of the most prevalent tumor types in our database, including NSCLC, CRC, and breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By designing the sensitivity study samples with 2 monitorable alterations, we sought to estimate lowest possible sensitivity of the assay and show it to be >97.3% in low ctDNA samples (5–10 MTM/mL). Sensitivity and precision of the assay will be less reliable at lower levels of ctDNA, however recent data suggests the assay is capable of detecting ctDNA down to the 0.4 MTM/mL level in metastatic colorectal cancer [ 2 ], and the performance of assay is sufficient to identify response to immunotherapy in patients with metastatic cancer [ 13 , 35 ] To address the possible limitation of evaluable patients, we show that 90.0% of patients with tissue CGP would have ≥2 monitorable alterations ( Fig 2B ). This was consistent among many of the most prevalent tumor types in our database, including NSCLC, CRC, and breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating tumor DNA (ctDNA) in blood is an emerging prognostic and predictive biomarker for managing patient treatment decisions, informing risk of recurrence and response to therapy in early and late-stage disease [1][2][3][4]. Risk-assessment strategies in the adjuvant and perioperative setting are limited, leading to uncertainty around treatment planning.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of liquid biopsy samples for “re-challenge” strategy with EGFR inhibitors in RAS wild-type cases may be considered the most promising area for CRC patients. Other important applications of liquid biopsy regarding detection of ctDNA in the CRC setting are: (i) analysis of minimal residual disease (MRD) as a prognostic factor and for adjuvant therapy selection 68 , 72 , (ii) identification of RAS and BRAF mutations in the absence of an adequate tissue biopsy in the metastatic setting, and (iii) evaluation of the prognostic significance of cfDNA in early-stage disease 71 , 73 . Technical administration of liquid biopsy samples requires comprehensive, ultra-deep technologies, like NGS platforms or digital PCR (dPCR) systems 74 enabling to detect cancer-related molecular alterations from scant samples.…”
Section: Liquid Biopsymentioning
confidence: 99%
“…In multivariate analyses, ctDNA+/− and ctDNA−/− were independently associated with improved RFS compared to ctDNA+/+ (ctDNA+/−: HR 0.21, 95% CI 0.08–0.53; ctDNA−/−: HR 0.21, 95% CI 0.08–0.56) [ 57 ]. ctDNA status has also been demonstrated to be a prognostic factor after local therapies of CRLM, such as stereotactic radiotherapy and radiofrequency ablation [ 58 ]. Another prospective study with 105 patients with CRLM who underwent curative-intent hepatectomy and tested for ctDNA within 180 days postoperatively showed that a postoperative ctDNA-positive result was associated with multiple CRLM and with co-mutation RAS/TP53 [ 56 ].…”
Section: Mrd In Metastatic Colorectal Cancermentioning
confidence: 99%